Rural EFL Learners’ Insights Towards Technology Use Tendency in Language Learning - Heri Mudra; Ahmad Jamin (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
Technology has empowered rural school learners to learn English actively without any hesitation. This study aimed to describe how rural EFL learners state their emotional and behavioral approaches to learning English using technology. A total of 119 learners who were registered in rural schools voluntarily participated in a survey study. Quantitative data were collected as an online survey by administering a scale on technology use tendency. Percentages were focused on determining learners’ tendency levels. The results reveal that rural EFL learners tended to be involved in technology integration classes. Such technology increased enthusiasm, participation, creativity, and task completion. However, some learners did not align with the integration, as technology was believed to support learning but not replace a teacher. Discussion and implied recommendations are provided to emphasize the results.